2018
DOI: 10.1242/jcs.221317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of integrin αVβ5 clustering in flat clathrin lattices

Abstract: The family of integrin transmembrane receptors is essential for the normal function of multicellular organisms by facilitating cellextracellular matrix adhesion. The vitronectin-binding integrin αVβ5 localizes to focal adhesions (FAs) as well as poorly characterized flat clathrin lattices (FCLs). Here, we show that, in human keratinocytes, αVβ5 is predominantly found in FCLs, and formation of the αVβ5containing FCLs requires the presence of vitronectin as ligand, Ca 2+ , and the clathrin adaptor proteins ARH (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(122 citation statements)
references
References 80 publications
10
111
0
1
Order By: Relevance
“…It was shown that their presence was cell type specific and that they were limited to the ventral plasma membrane 36 . This side-specific localization and the fact that clathrin-coated plaques are in close contact with the substrate 31,32 as well as associated with the ECM receptors integrins 27,32–34 strongly suggest a function in cell adhesion. Aiming at characterizing this function, we exploited the human glioblastoma U373 cell line previously reported to display clathrin-coated plaques 36,37 .…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…It was shown that their presence was cell type specific and that they were limited to the ventral plasma membrane 36 . This side-specific localization and the fact that clathrin-coated plaques are in close contact with the substrate 31,32 as well as associated with the ECM receptors integrins 27,32–34 strongly suggest a function in cell adhesion. Aiming at characterizing this function, we exploited the human glioblastoma U373 cell line previously reported to display clathrin-coated plaques 36,37 .…”
Section: Resultsmentioning
confidence: 80%
“…Previously, it was suggested that proteins of the clathrin pioneer module that initiate CME and lead to the recruitment of clathrin to the plasma membrane, e.g. FCHO1/2 and Eps15/R, stabilize the clathrin lattice early during coat formation and help to establish the hexagonal organization of flat clathrin structures 34,5860 . Therefore, we investigated if early clathrin-related proteins of the pioneer module are important for clathrin-coated plaque formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations